Konsep Seni Islam Sayyid Husein Nasr - A. Khudori Soleh (el Harakah: Jurnal Budaya Islam, 2010)
Sayyid Husein Nasr divided art into three parts: pure art, traditional art and religious art. Islamic art included on pure art, relates to the principle of cosmos unity and principle of individual life unity and society. Because of that, according to Nasr, thinking about Islamic art is not based on material and social political experience that scope on inner reality of al Quran. In other hand, Islamic art also based on wisdom or knowledge that inspired of spiritual values, therefore Islamic art can be made as a result of khazain al ghaib. Because of that, Islamic art always reflected on religious values and explained of spiritual qualities. Actually, there are four functions which carry out by Islamic art. (1) Aims a blessed as cause of spiritual relation with Islamic spiritual dimension; (2) Remembering presence of the God in everywhere peoples are; (3) As criteria to evaluate social movement, cultural or politic that really Islamic or not; (4) to determined step of intellectual relation and religious of society.Sayyid Husein Nasr membagi seni menjadi tiga bagian: seni murni, kesenian tradisional dan seni religius. Seni Islam termasuk seni murni, berkaitan dengan prinsip kesatuan kosmos dan prinsip persatuan kehidupan individu dan masyarakat. Karena itu, menurut Nasr, pemikiran tentang seni Islam tidak didasarkan pada pengalaman material dan sosial politik yang lingkup realitas batin al quran. Di sisi lain, seni Islam juga didasarkan pada hikmat atau pengetahuan yang mengilhami nilai-nilai spiritual, oleh karena itu seni Islam bisa dijadikan khazirah al ghaib. Karena itu, seni Islam selalu tercermin pada nilai-nilai agama dan menjelaskan kualitas spiritual. Sebenarnya ada empat fungsi yang dilakukan oleh seni Islam. (1) Bertujuan diberkati sebagai penyebab hubungan spiritual dengan dimensi spiritual Islam; (2) Mengingat keberadaan Tuhan di mana-mana orang-orang; (3) Sebagai kriteria untuk mengevaluasi gerakan sosial, budaya atau politik yang benar-benar Islami atau tidak; (4) menentukan langkah relasi intelektual dan religius masyarakat.